Discrete mathematics for beginners - Liew, Chin Ying; Ling, Siew Ching; Voon, Li Li (UiTM Press, 2025)
Discrete Mathematics for Beginners addresses fundamental concepts essential for novices enrolled in a discrete mathematics course. Beginning with Set Theory, the book explains the fundamentals of sets, their operations, laws, and real-world applications. It then delves into counting principles, offering discussions on permutations, combinations, and the Binomial Theorem. It continues with Functions and Relations, focusing on understanding Cartesian products, relation properties, and functions. The chapter on Directed Graphs presents fundamental concepts and properties related to graphs and paths, trees, Eulerian and Hamiltonian paths, and circuits. Next, the chapter on logic discusses logical statements, truth tables, laws of logic, the construction of sound arguments, and rules of inference. Finally, Basic Number Theory is illustrated through sequences and summations, mathematical induction, and recursive definitions. With succinct summaries and revision exercises, the book is a comprehensive companion in equipping the readers with the skills needed to master key topics in discrete mathematics.